Acute Lung Injury in Fatal Paraquat Poisoning: A Case Report (Journal of Forensic Medicine & Toxicology, 2025)
Paraquat is a highly toxic herbicide associated with significant morbidity and mortality following ingestion, primarily due to its profound pulmonary toxicity. Acute lung injury (ALI) and progressive pulmonary fibrosis represent the hall mark pathological features, often leading to respiratory failure and death. We report a case of fatal paraquat poisoning in a young adult who presented with gastrointestinal symptoms and rapidly deteriorated despite supportive management. Laboratory investigations revealed multi-organ involvement, and imaging demonstrated diffuse pulmonary infiltrates consistent with ALI. Despite intensive care, the patient developed severe hypoxemia and succumbed within days of ingestion. This case underscores the challenges in managing paraquat poisoning, as no specific antidote exists and therapeutic strategies remain largely supportive. Early recognition, aggressive decontamination, and novel treatment modalities may improve outcomes; however, prognosis remains poor in cases with significant exposure. Clinicians must maintain high suspicion and counsel regarding the lethal potential of paraquat ingestion.
Keywords: Paraquat; Poisoning; Toxicology; Acute Lung Injury